2302-practice-final-soln

# Our final answer is therefore l f = 1 − e s 1 s 1 e

This preview shows pages 6–9. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Our final answer is therefore L { f } = 1 − e- s- 1 s +1 + e- s − e- 2 s s 1- e − 2 s . 7 Find the first six terms in the power series expansion at x = 0 for the general solution to the differential equation ( x 2 + 1) y ′′ + y = 0. Solution: We need to find the first six terms, so we make the following substitutions y = a + a 1 x + a 2 x 2 + a 3 x 3 + a 4 x 4 + a 5 x 5 + ... , y ′ = a 1 + 2 a 2 x + 3 a 3 x 2 + 4 a 4 x 3 + 5 a 5 x 4 + ... , y ′′ = 2 a 2 + 6 a 3 x + 12 a 4 x 2 + 20 a 5 x 3 + ... , MAP 2302, Fall 2011 — Final Exam Review Problems 7 Now we make the substitution: ( x 2 +1) y ′′ + y = ( x 2 +1)(2 a 2 +6 a 3 x +12 a 4 x 2 +20 a 5 x 3 + ... )+( a + a 1 x + a 2 x 2 + a 3 x 3 + a 4 x 4 + a 5 x 5 + ... ) . We now expand to get (2 a 2 + a ) + (6 a 3 + a 1 ) x + (12 a 4 + 2 a 2 + a 2 ) x 2 + (20 a 5 + 6 a 3 + a 3 ) x 3 + ··· = 0 Note that we can stop here because we have enough equations to solve for a 2 , a 3 , a 4 , and a 5 in terms of our two arbitrary constants, which will be a and a 1 (these are always the arbitrary constants in power series solutions of second order equations!). Our system of equations is then 2 a 2 + a = 0 , 6 a 3 + a 1 = 0 , 12 a 4 + 3 a 2 = 0 , 20 a 5 + 7 a 3 = 0 . We proceed from top to bottom. The first equation shows that a 2 =- a / 2 . The second shows that a 3 =- a 1 / 6 . The third then becomes 12 a 4 + 3 a 2 = 12 a 4- 3 a / 2 = 0, so a 4 = a / 8 . The fourth becomes 20 a 5 + 7 a 3 = 20 a 5- 7 a 1 / 6 = 0, so a 5 = a 1 / 120 . Our final answer is therefore y = a + a 1 x- a 2 x 2- a 1 6 x 3 + a 8 x 4 + a 1 120 x 5 + ··· . 8 Find the singular points of the equation ( x 2- 1) y ′′- ( x- 1) y ′ + 17 y = 0 and classify them as regular or irregular. Solution: To find the singular points, we first write the differential equation in standard form: y ′′- x- 1 x 2- 1 y ′ + 17 x 2- 1 y = 0 . From this we see that the singular points are x = ± 1. We need to test each of them separately. The point x = 1 will be a regular singular point if both of the limits lim x → 1 ( x- 1) x- 1 x 2- 1 and lim x → 1 ( x- 1) 2 17 x 2- 1 exist. It is easy to check that both of these limits exist (in fact, they are both equal to 0), so x = 1 is a regular singular point. MAP 2302, Fall 2011 — Final Exam Review Problems 8 For x =- 1, our two limits are lim x →− 1 ( x + 1) x- 1 x 2- 1 and lim x →− 1 ( x + 1) 2 17 x 2- 1 . Again, both limits exist (the first equals 1, the second equals 0), so x =- 1 is also a regular singular point. 9 A 2 kg mass is attached to a spring with stiffness k = 10 N/m. The mass is displaced 1 m to the right of the equilibrium point and given an initial leftward velocity of 1 m/s. Let y ( t ) denote the position of the spring at time t seconds, where positive y indicates distance to the right of the equilibrium point. Solve for y , express it in the form y = A sin( ωt + φ ), and then clearly indicate the amplitude, period, and phase angle of this motion.clearly indicate the amplitude, period, and phase angle of this motion....
View Full Document

{[ snackBarMessage ]}

### Page6 / 15

Our final answer is therefore L f = 1 − e s 1 s 1 e s −...

This preview shows document pages 6 - 9. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online